2009
DOI: 10.1097/jcp.0b013e3181a497d7
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Pilot Study of Galantamine to Improve Cognitive Dysfunction in Minimally Symptomatic Bipolar Disorder

Abstract: Episodic memory performance was improved in the galantamine treatment group but did not improve in the placebo group. In contrast, performance on 2 of the processing speed measures showed significant improvement in the placebo condition, whereas that of the patients treated with galantamine did not improve. Galantamine may thus have specific benefits for episodic memory, but not processing speed, in patients with cognitive impairment as part of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Quality assessed with the Jadad scale ( Table 1; eTable 1) indicated that 4 studies Keck et al, 2009;Kelly, 2008b;Schrauwen and Ghaemi, 2006) had no quality (Jadad's scale=0), 4 (Gildengers et al, 2008;Iosifescu et al, 2009;Keck et al, 2009;Koukopoulos et al, 2012) had low quality (Jadad's scale=1), 1 (Iosifescu et al, 2009) had medium quality (Jadad's scale=2), and 5 (Ae et al, 2006;Anand et al, 2012;Ghaemi et al, 2009;Lee et al, 2014) were of high quality (Jadad's scale>3). All the studies with high quality were also RCTs, while among the studies with other designs, only 1 (Iosifescu et al, 2009) included a control group, reaching a medium quality.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Quality assessed with the Jadad scale ( Table 1; eTable 1) indicated that 4 studies Keck et al, 2009;Kelly, 2008b;Schrauwen and Ghaemi, 2006) had no quality (Jadad's scale=0), 4 (Gildengers et al, 2008;Iosifescu et al, 2009;Keck et al, 2009;Koukopoulos et al, 2012) had low quality (Jadad's scale=1), 1 (Iosifescu et al, 2009) had medium quality (Jadad's scale=2), and 5 (Ae et al, 2006;Anand et al, 2012;Ghaemi et al, 2009;Lee et al, 2014) were of high quality (Jadad's scale>3). All the studies with high quality were also RCTs, while among the studies with other designs, only 1 (Iosifescu et al, 2009) included a control group, reaching a medium quality.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…A small RCT in 16 participants with BD I and II minimally symptomatic reported that compared to placebo (n=10) galantamine (n=6) showed no significant effect of galantamine on depression, mania, cognitive performance, and global functioning (assessed with GAF) (Ghaemi et al, 2009).…”
Section: Galantaminementioning
confidence: 99%
See 3 more Smart Citations